PENINGKATAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI PENERAPAN MODEL FUN LEARNING BERBASIS MEDIA AUDIO VISUAL PADA SISWA TUNAGRAHITA DI SMPLB NEGERI SIDOMULYO - Muzekki; Meriyati; Heny Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the improvement of learning motivation in Islamic Religious Education (PAI) through the implementation of a fun learning model based on audio-visual media for students with intellectual disabilities at SMPLB Negeri Sidomulyo. The background of this research is based on the low learning motivation of students with intellectual disabilities, influenced by cognitive limitations, the lack of varied instructional models, and the minimal use of engaging learning media. This study employs a descriptive qualitative approach with a case study design. The research subjects include the principal, PAI teacher, vice principal for curriculum, and students. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing, with validity tested through source and technique triangulation. The results show that the implementation of the audio-visual-based fun learning model is carried out in three stages: planning, implementation, and evaluation. During the implementation stage, learning takes place in a multisensory manner through the use of videos, demonstrations of worship practices, educational games, and the application of modeling, guided practice, and positive reinforcement methods. This model has been proven to improve students’ learning motivation, as indicated by increased attention, active participation, enthusiasm, confidence in interaction, and persistence in learning. However, the improvement in motivation is not evenly distributed due to differences in students' intellectual and adaptive abilities. In addition, several challenges were identified, including limited learning media, heterogeneous student abilities, and the need for intensive assistance. Therefore, this model is considered effective and relevant as an innovative, enjoyable, and humanistic learning strategy.